Structural, thermoelectric, and magnetic properties of pure and Ti-doped Ca3Co4O9 ceramic compounds - BOYRAZ, CİHAT (My University, 2023)
The effect of the Ti element on the incommensurately layered thermoelectric oxide material Ca3Co4O9 is investigated. This study compares the structural, morphological, thermoelectric, and magnetic properties of Ca3(Co3.7Ti0.3)O9 composition to the pristine Ca3Co4O9. No significant enhancement of the Seebeck coefficient compared to Ca3Co4O9 is observed in the Ti-doped sample. The magnetic properties of the pristine and Ti-doped Ca3Co4O9 are detailed, and the possible correlations between pristine and Ti-doped Ca3Co4O9 are established. In M-H measurements, the effect of Ti in low temperatures revealed a magnetic phase transition due to two sublattices exhibiting wavy behavior. For each sample, magnetic inhomogeneity in the long-range ferromagnetic ordering, which is clear almost before 19 K, is observed through FC and ZFC curves. The findings on the physical properties of both samples are discussed, considering the previously published results.
Keywords: Structural and magnetic properties; thermoelectricity; Ti-doped Ca3Co4O9